2021
DOI: 10.1186/s12891-021-04586-x
|View full text |Cite
|
Sign up to set email alerts
|

Cemented hemiarthroplasty versus proximal femoral nail antirotation in the management of intertrochanteric femoral fractures in the elderly: a case control study

Abstract: Background The treatment for intertrochanteric femoral fractures (IFF) among the elderly has been a controversial topic. Hemiarthroplasty (HA) and proximal femoral nail antirotation (PFNA) have their own advantages in the management of IFF. Hence, this study aims to compare and analyze differences in the effectiveness of both procedures on IFF among the elderly. Methods Overall, 99 patients (81.09 ± 8.29 years; 68 women) underwent HA or PFNA from J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Recent studies have suggested that LCHA replacements have fewer postoperative complications than intramedullary nailing for treating IFF in older adults [5,8,23]. However, Tang et al found no signi cant difference in postoperative complications between the two groups of patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that LCHA replacements have fewer postoperative complications than intramedullary nailing for treating IFF in older adults [5,8,23]. However, Tang et al found no signi cant difference in postoperative complications between the two groups of patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…Sinno 2010 [86] ✓ (A) Bansal 2019a [50] ✓ (A) Jin 2021 [67] ✓ (A) Soreide 1979 [87] − Magu 2008 [75] ✓ (A) Mansukhani 2017 [102] ✕ Table 3. Counts of reported surgical-related barriers and facilitators with a positive association (), negative association (), or absence of an association (-), with weight bearing after hip fracture surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Cemented endoprostheses can be beneficial in patients with a thin cortical bone structure to reduce the risk of periprosthetic fractures. Cement application, on the other hand, may increase cardiopulmonary risks in such patients [ 26 , 27 ]. Aside from the bone loss, there are studies suggesting the use of larger femoral stems with long calcar support, due to the wide femoral canal observed in older adult patients [ 26 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%